Forms in which the property of the State Treasury Agricultural Property Stock may be developed following the amendments to the regulations made in 2016 - Suchoń, Aneta (Przegląd Prawa Rolnego, 2018)
The aim of the author of the article was to determine the impact of the amendments to the legal regulations, especially those introduced by the Act of 14 April 2016 on suspending the sale of real estate from the State Treasury Agricultural Property Stock, on the forms of property development. In particular, it is to determine which of these forms dominate and to indicate the legal conditions related to their functioning. Among other things, it has been noted the sale of the property from the State Treasury Agricultural Property Stock has significantly decreased in comparison with the years 2009–2014, while the area of agricultural land being leased is growing. The amendments to the regulations have therefore strengthened the role of leasing in rural relations. Moreover, the National Agricultural Support Centre enjoys greater rights when selling agricultural property from the State Treasury Agricultural Property Stock, not only before but also after the contract of sale is finalised. The same is true when it comes to the exercise of the pre-emption right to acquire shares in companies owing agricultural property.